Strategi Menciptakan Budaya Dan Iklim Organisasi Yang Positif - Sentia Devi; Tahany Nabila Putri (CV. ITTC INDONESIA, 2025)
This article discusses the importance of a positive organizational culture and climate in achieving company goals. A common phenomenon observed is organizations facing issues such as high employee turnover or stagnant productivity, despite significant investments in technology and processes. This indicates underlying problems within the work environment and organizational values. This study explores how a positive organizational culture and climate can enhance employee performance, loyalty, and retention. Furthermore, various factors influencing the formation of organizational culture and climate, such as leadership style and open communication, are examined. The article also identifies frequently encountered challenges, ranging from inter-individual differences to global-scale issues, and proposes several concrete strategies. These strategies include providing recognition and rewards, continuous development and training, effective communication, and efforts to build a strong organizational culture to create a conducive and sustainable work environment.